Hard-decision Staircase Decoder in 28-nm Fully-Depleted Silicon-on-Insulator - Hurtic, Elma; Lillmaa, Henri (My University, 2016)
The continuous advancements in optical communication channels have propelled the development of new error-correcting codes, e.g., staircase codes, which belong to a class of hard-decision algebraic codes. The staircase code is a new in-line error-correcting code that promises near-capacity performance. In this Master’s Thesis BCH component codes and staircase codes are analysed in MATLAB. A bit-parallel BCH component code decoder is described in VHDL and synthesised in a 28-nm fully-depleted silicon-on-insulator (FD-SOI) library. Based on synthesis and simulation, the area and power consumption of staircase decoders for 100 Gbps throughput are estimated.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science